2018
DOI: 10.1038/s41598-018-23634-6
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the bacterial communities associated with the harmful microalgae Alexandrium tamarense and Cochlodinium polykrikoides using nanopore sequencing

Abstract: Interactions between microalgae and bacteria are often obligatory for harmful algal blooms (HABs). Here, we investigated the specific bacterial communities associated with Alexandrium tamarense and Cochlodinium polykrikoides, which cause ecological and economic damage during their blooms. To this end, the bacterial metagenome was selectively isolated from the two dinoflagellates and subsequently used for 16S rRNA analysis via the Nanopore MinION and Illumina sequencing platforms. Although the full-length 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…A prime example is the MinION™ sequencer from Oxford Nanopore Technologies, which is capable of producing long sequences with no theoretical read length limit [9][10][11]. MinION™ sequencing targets the entire 16S rRNA gene, allowing the identification of bacteria with more accuracy and sensitivity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A prime example is the MinION™ sequencer from Oxford Nanopore Technologies, which is capable of producing long sequences with no theoretical read length limit [9][10][11]. MinION™ sequencing targets the entire 16S rRNA gene, allowing the identification of bacteria with more accuracy and sensitivity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies targeting the full-length 16S rRNA gene have already been performed using nanopore sequencing to: i) characterize artificial and already characterized bacterial communities (mock community) [1517]; ii) characterize complex microbiota samples, from mouse gut [18], wastewater [19], microalgae [20] and dog skin [21]; and iii) characterize the pathogenic agent in a clinical sample [2224]. On the other hand, only two studies have been performed using the whole rrn operon to characterize mock communities [25] and complex natural communities [26].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the study of microbiota, several studies have been dedicated to compare taxonomical analysis derived by this technology with Illumina sequencing, and have shown that error rate has been compensated with larger fragments, providing in some cases higher taxonomical resolution 26,27 . Although the error rate remains the main limitation to the expansion of this sequencing methodology, it has been successfully applied in several species and tissues, identifying the microbiota present in complex samples from terrestrial 28,29 and aquatic environment 23,30 . Notably, nanopore sequencing has been applied to understand the interactions of human diseases 31 , environmental samples obtained from glacier regions 23 , ocean water column 32 and to identify the bacterial community associated with harmful microalgae 30 , and these studies demonstrate the potential and applicability of nanopore sequencing for microorganism detection in all environments.This study aimed to characterize the microbiota community associated with the salmon's ectoparasite Caligus rogercresseyi obtained from different geographical regions, using third-generation sequencing technology based on nanopore sequencing of full 16S rRNA gene.…”
mentioning
confidence: 99%